Hadith #6172 - Sahih Muslim - Abu al-Matwas أبو المطوس (Sahih Muslim)
We were in the house of Abu Musa along with some of the companions of ‘Abdullah and they were looking at the Holy Book. ‘Abdullah stood up, whereupon Abu Mas’ud said: I do not know whether Allah’s Messenger, (ﷺ) has left after him one having a better knowledge (of Islam) than the man who is standing. Abu Musa said: If you say this, that is correct, because he had been present when we had been absent and he was permitted when we were detained.
Grade: Sahih